2012
DOI: 10.1261/rna.028498.111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the enzyme responsible for N1-methylation of pseudouridine 54 in archaeal tRNAs

Abstract: ABSTRACTtRNAs from all three kingdoms of life contain a variety of modified nucleotides required for their stability, proper folding, and accurate decoding. One prominent example is the eponymous ribothymidine (rT) modification at position 54 in the T-arm of eukaryotic and bacterial tRNAs. In contrast, in most archaea this position is occupied by another hypermodified nucleotide: the isosteric N1-methylated pseudouridine. While the enzyme catalyzing pseudouridine formation at this position is known, the pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…As no pseudouridine-specific mapping was performed (63,64), the localization of this modification to positions 54 and 55 of specific tRNAs is expected but not verified here. The DUF358 SPOUT-methyltransferase MJ1640 (renamed TrmY) acts in concert with Pus10 to catalyze the biosynthesis of m 1 ⌿ at position 54 (65)(66)(67). Data consistent with m 1 ⌿(54) were obtained from tRNA GAC Val .…”
Section: Discussionmentioning
confidence: 89%
“…As no pseudouridine-specific mapping was performed (63,64), the localization of this modification to positions 54 and 55 of specific tRNAs is expected but not verified here. The DUF358 SPOUT-methyltransferase MJ1640 (renamed TrmY) acts in concert with Pus10 to catalyze the biosynthesis of m 1 ⌿ at position 54 (65)(66)(67). Data consistent with m 1 ⌿(54) were obtained from tRNA GAC Val .…”
Section: Discussionmentioning
confidence: 89%
“…Recently, two groups independently identified new SPOUT tRNA methyltransferases (Mja 1640 from Methanocaldococcus jannaschii and Hvo 1989 from Haloferax volcanii) producing the m 1 ⌿54 modification in archaeal tRNA (43,44). These proteins, which share homology with the catalytic domain of 18 S rRNA methyltransferase (Nep1), which gives rise to m 1 acp 3 ⌿ (52, 53), are mainly formed by the catalytic domain (42)(43)(44). This observation is in line with our current findings that a small part(s) of the catalytic domain discriminates the substrate RNA.…”
Section: Discussionmentioning
confidence: 99%
“…These studies established the structural foundation of SPOUT enzymes (Anantharaman et al, 2002 ; Tkaczuk et al, 2007 ), which can be identified on the basis of the topological-knot structure. To date, several tRNA methyltransferases have been identified as members of the SPOUT superfamily on the basis of crystal structures (Kuratani et al, 2008 ; Chen and Yuan, 2010 ; Chatterjee et al, 2012 ; Wurm et al, 2012 ; Shao et al, 2013 ) or structures predicted from amino acid sequences and conserved motifs (Renalier et al, 2005 ; Purta et al, 2006 ; Tkaczuk et al, 2007 ; Kempenaers et al, 2010 , and Figure 4B ). Furthermore, the SPOUT superfamily is expanding beyond the SpoU and TrmD families: novel enzymes such as an archaeal Trm10 homolog (Kempenaers et al, 2010 ) and TrmY (Chen and Yuan, 2010 ; Chatterjee et al, 2012 ; Wurm et al, 2012 ) have been identified.…”
Section: Structures Of Trna Methyltransferasesmentioning
confidence: 99%